Contribuições da arquitetura para a "indústria cultural" de Theodor Adorno e Max Horkheimer - Ana Paola da Silva Alves (2006)
This dissertation investigates the established relations between Architecture and The Culture Industry", analysed by Theodor Adorno and Max Horkheimer in the 1940s which still with its full vigour nowadays. This is done by developing an in-depth study of some of the main ideas that involve the concept of culture industry and the so-called "administered society", such as standardization, the appropriation of artistic instances, fetishism and the usurpation of the capacity of individuals judgment. From the authors argument which links the emergence of this industry with a model of instrumental rationality, harnessed to a systematic organization which imposes a standard of living to men based on practical and economic purposes, it is also analysed how rationalization process, whereby the western society went through, happened in Architecture and totally modified the processes of its conception, becoming quite in tune with the proper dynamics of the culture industry. In last instance this paper verifies the coincidences between the capitalist and architectural ideologies, which consist of the instrumentalization of architecture, that is to say, in its use aiming to reach economic objectives, to guarantee the control of the citizens inside the society, besides the maintenance of the status quo.